Second first impressions : a novel - Thorne, Sally, 1981- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
A spoiled, tattooed rich man reluctantly agrees to become an assistant to two casually exploitative nonagenarians before unexpectedly catching the eye of the property's serious-minded manager.